Procedimiento para la identificación de peligros y evaluación de riesgos laborales en la Alcaldía municipal de Gutiérrez Cundinamarca (2021)
The Municipal Mayor's Office of Gutiérrez Cundinamarca is a municipal administration entity belonging to the executive branch, in which there is a need to define the procedure for the identification of hazards and risk assessment in accordance with the provisions of Resolution 0312 of 2019 and in accordance with the Occupational Health and Safety Management System (SG SST), for which it will be carried out and has as one of its objectives to develop the self-report format of health and work conditions; In order to guarantee that later the entity can correctly fill out the hazard identification and risk assessment matrix for all the dependencies and employees of the mayor's office and finally by generating some control measures for said risks.